VISUAL AND VERBAL HUMOR ON FACEBOOK AND INSTAGRAM - Yanti, Ferda; Abdullah, Abdullah (Journal of English Literature and Linguistic Studies, 2024)
This research discusses visual and verbal humor on Facebook and Instagram and the meaning of the humor found on it. It aims to analyze verbal humor on Facebook and Instagram using theory of Shade (1996) to analyze the verbal humor types and theory of Berger (2020) to identify the meaning of visual and verbal humor found in the object. The research method used in this study was a qualitative descriptive method. The researchers analyzed visual and verbal humor on 5 accounts on Facebook and 8 accounts on Instagram. The result of this research shows that there are 30 numbers of visual and verbal humors found in Facebook and Instagram. It is found in 8 out of 12 types of verbal humor and 3 out of 4 types of visual humor. It can be concluded that there are several types found on Facebook and Instagram social media. Researchers observed five accounts on Facebook and 8 accounts on Instagram in this study. From these accounts the researchers found verbal humor which are  joke (4 from Instagram, 1 from Facebook), pun (1 from Facebook, 2 from Instagram), riddles (2 from Facebook, 1 from Instagram), sarcasm (2 from Instagram), satire (1 from Instagram), parody (1 from facebook), wit (1 from facebook, 1 from instagram), and irony (1 from instagram). For visual humor there are several types found, among others, impersonation (2 from Facebook, 4 from Instagram), practical jokes (1 from Instagram, 2 from Facebook), slapstick (1 from Instagram, 2 from Facebook). The researchers also found that there were several types of humor that did not exist in some of the selected accounts, such as limerick, anecdote, tall tales, farce, and mime. The researchers also found that the meaning of humor that make them funny are mostly the meaning of absurdity (7), accident (2), before/after (4), riddle (3), pun (3), imitation (4), repartee (2), ridicule (1), misunderstanding (1), satire (1), parody (1), and irony (1).